2006
DOI: 10.1007/s10529-006-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Bacterial Consortium Enriched from an Oilfield that Degrades Phenanthrene

Abstract: Characterization of functional and phylogenetic genes was carried out on a bacterial consortium, enriched from a water treatment system of an oilfield, that could use phenanthrene as the sole carbon source. The mixed culture degraded 130 mg phenanthrene l )1 in 16 days, which is significantly faster than previously reported pure cultures. The existence of catabolic genes (nahAc, C23O) in the mixed culture was quantitated by most probable number PCR. The plasmid encoding phenanthrene catabolic genes increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Therefore, the synergistic effects on the PHE degradation in the consortia cannot be attributed to the metabolic products of one strain in the consortia. Studies have reported that synergistic effects or enhancement of degradation efficiency in consortia can result from: (1) cooperative effects due to different complementary biochemical PHE degradation pathways in the strains (Wang et al, 2006); (2) assimilation of PHE onto cell membrane and changes of cell hydrophobicity by excreted substances such as biosurfactants (Phale et al, 1995;Prabhu and Phale, 2003;Andreoni et al, 2004); (3) elimination of PHE metabolites by one strain that inhibit other strains (Bouchez et al, 1999); and (4) significant increment of biomass using surfactants as a primary carbon source (Kim and Weber, 2003). Which if any of these mechanisms explain the synergistic effects on PHE degradation in the consortia remains to be tested.…”
Section: Synergistic Effect In the Consortiamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the synergistic effects on the PHE degradation in the consortia cannot be attributed to the metabolic products of one strain in the consortia. Studies have reported that synergistic effects or enhancement of degradation efficiency in consortia can result from: (1) cooperative effects due to different complementary biochemical PHE degradation pathways in the strains (Wang et al, 2006); (2) assimilation of PHE onto cell membrane and changes of cell hydrophobicity by excreted substances such as biosurfactants (Phale et al, 1995;Prabhu and Phale, 2003;Andreoni et al, 2004); (3) elimination of PHE metabolites by one strain that inhibit other strains (Bouchez et al, 1999); and (4) significant increment of biomass using surfactants as a primary carbon source (Kim and Weber, 2003). Which if any of these mechanisms explain the synergistic effects on PHE degradation in the consortia remains to be tested.…”
Section: Synergistic Effect In the Consortiamentioning
confidence: 99%
“…Although pure cultures of several PAH-degrading bacteria can readily utilize PAHs as a carbon source (Rodrigues et al, 2005;Kim et al, 2007), degradation results may improve if a mixed bacterial culture or bacterial-fungal consortium was used (Bouchez et al, 1999;Boonchan et al, 2000;Li et al, 2008). Generally, biodegradation using a pure strain does not represent the actual behavior of environmental microorganisms during bioremediation in natural PAH-contaminated soils, because in nature, bioremediation depends on cooperative metabolic activities of mixed microbial populations (Boonchan et al, 2000;Wang et al, 2006). To understand the interactions among microorganisms in mixed bacterial systems, analysis of population dynamics using cultureindependent techniques is required.…”
Section: Introductionmentioning
confidence: 99%
“…First, mixed bacterial cultures could relieve the inhibition of PAHs on the growth of some PAH-degrading bacteria strains, thus increasing the degradation rates (Bouchez et al, 1995). Second, the cooperation among different bacterial genotypes in the mixed cultures would possibly result in diverse degradation pathways of PAHs, thus leading to a fast degradation (Wang et al, 2006). Third, the mixed bacterial cultures could perform a complete degradation pathway of PAHs, since some strains were capable of degrading metabolites that accumulated when the parent PAHs were degraded by other strains (Bouchez et al, 1999;Luan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, insufficient biological information regarding the regulation of growth and metabolism in various microbial communities restricts development in the site-specific mineralization process. Similarly, the bioremediation of xenobiotic compounds either ex situ or in situ by pure isolates does not represent an actual behaviour of the microorganisms; however, it depends on cooperative metabolic activities of mixed microbial population [61][62][63]. Under these conditions biodegradative potential of all microbes can be crossed with the all known compounds and in silico bioremediation helps to predict the destiny of a compound whether partially or fully degraded to non toxic compounds.…”
Section: Discussionmentioning
confidence: 99%